The Effect Of Training, Communication On Turnover Intention Mediated By Job Satisfaction In Gen Z Employees In Pontianak City - Ambong, Ambong; Ginting, Sunardi (International Enterprise Integration Association, 2025)
This study examines the effect of job training, communication on turnover intention mediated by job satisfaction in the Gen Z workforce in Pontianak City with 208 respondents. This research is quantitative in nature which uses snow ball technique in data collection. The data obtained is processed using WarpPLS 8.0. The results of this study indicate that job training, communication has a significant positive effect on turnover intention, job satisfaction has a significant negative effect on turnover intention, job training, communication has a significant positive effect on job satisfaction, and job satisfaction can significantly mediate the effect of job training, communication on turnover intention.